The Difference in Lactobacillus plantarum Density on the Fermentation Process of Cassava Leaves (Manihot utillisima) as Substance for Plant-Based Protein - Priyandaru Agung Eko Trapsilo; Anik Martinah Hariati; Titik Dwi Sulistiati (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightCassava leaves (Manihot utillisima) identification and analysisObserving the content of anti-nutritional cyanide (HCN) in cassava leavesOrganoleptic testing in the fermentation process of Lactobacillus plantarum bacteria against cassava leaves (Manihot utilissima)Knowing the nutritional content of cassava leaves, after fermentation process that use the different Lactobacillus plantarum bacteriaKnowing the nutritional content of fermented cassava leaves (Manihot utilissima)AbstractCassava leaves (M. utilissima) are well used as a staple ingredient for feeding livestock mainly for high nutrient content especially protein which is 27%. The main problem in the use of cassava leaves as fish feed ingredients is its high fiber content, making it difficult to be digest by fish. The main purpose of this research was that fermented cassava leaves by using L. plantarum could increase its protein content. This research was conducted by adding the different concentrations of L. plantarum which were 0 cell/ml, 1012 cells/ml, and 1013 cells/ml, 1014 cells/ml, and repeated three times. The result showed that L. plantarum with the concentration of 1014 cells/ml provides the best results overall in increasing protein content by 35.8% and physical characteristic test including scent, texture, hypha quantity, and water vapor provides the best result